Pharmacokinetics of mycophenolate mofetil in juvenile patients with autoimmune diseases. Issue 6 (2nd November 2019) - Nakaseko, Haruna; Iwata, Naomi; Yasuoka, Ryuhei; Kohagura, Toaki; Abe, Naoki; Kawabe, Shinji; Mori, Masaaki
Abstract: Objectives: This study aimed to determine the association between the dosage and pharmacokinetics of mycophenolate mofetil (MMF) in juvenile patients with autoimmune diseases. Methods: Totally, 29 patients were administered oral MMF. The blood concentrations of mycophenolate acid (MPA) at seven points, the area under the time–concentration curve (MPA–AUC0–12h ), the peak concentration ( C max ), and the time to peak concentration ( T max ) were measured. To obtain a dose-normalized MPA–AUC0–12h value, the actual measured MPA–AUC0–12h value was divided by the dose value of the morning administration corrected for body weight (BW) or body surface area (BSA). The patients were classified into three age groups (group 1, ≤10 years; group 2, >10–≤15 years; and group 3, >15 years), and pharmacokinetic parameters were compared among the groups. Results: In total, we obtained 37 measurements. The actual measured MPA–AUC0–12h values and the MPA–AUC0–12h values corrected for dose per BW and T max were lower in young patients. The MPA–AUC0–12h values corrected for dose per BSA and C max were comparable among all the groups. Conclusion: In patients with juvenile autoimmune diseases, determining MMF administration dosage according to BSA may facilitate MPA–AUC0–12h value prediction.